2008
DOI: 10.1016/j.bbr.2008.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific effects of anosmia and cloacal gland anesthesia on Fos expression induced in male quail brain by sexual behavior

Abstract: In rats, expression of the immediate early gene, c-fos observed in the brain following male copulatory behavior relates mostly to the detection of olfactory information originating from the female and to somatosensory feedback from the penis. However, quail, like most birds, are generally considered to have a relatively poorly developed sense of smell. Furthermore, quail have no intromittent organ (e.g., penis). It is therefore intriguing that expression of male copulatory behavior induces in quail and rats a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 81 publications
(132 reference statements)
0
25
0
Order By: Relevance
“…Neuronal activity, as measured by c-fos induction, is increased in the BNST after copulation, but not with appetitive behavior toward a female in male quail (Taziaux et al, 2006). However, this increase was not seen when the cloacal gland was anesthetized (Taziaux et al, 2008), suggesting that somatosensory information is important for this neuronal response to copulation. Further, the BNST also plays a role in reproduction in songbirds, as c-fos induction increases during courtship songs compared to noncourtship songs in male European starlings (Heimovics and Riters, 2006).…”
Section: Birdsmentioning
confidence: 90%
See 1 more Smart Citation
“…Neuronal activity, as measured by c-fos induction, is increased in the BNST after copulation, but not with appetitive behavior toward a female in male quail (Taziaux et al, 2006). However, this increase was not seen when the cloacal gland was anesthetized (Taziaux et al, 2008), suggesting that somatosensory information is important for this neuronal response to copulation. Further, the BNST also plays a role in reproduction in songbirds, as c-fos induction increases during courtship songs compared to noncourtship songs in male European starlings (Heimovics and Riters, 2006).…”
Section: Birdsmentioning
confidence: 90%
“…However, different subregions of the avian POA seem to differentially regulate appetitive and consummatory behavior in male quail as shown by lesion and immediate early gene studies (Balthazart et al, 1998a;Taziaux et al, 2006). Interestingly, c-fos immunoreactivity is markedly decreased in the region when olfactory cues are blocked (Taziaux et al, 2008), suggesting not only that sensory integration is important for neuronal activation in the POA, but also that olfactory information plays an important role in avian behavior. In male zebra finch, the dopaminergic cells within the POA exhibit increased c-fos induction after sexual encounters, but not after agonistic encounters (Bharati and Goodson, 2006), suggesting that dopamine plays an important role in regulating male sexual behavior, similar to mammals (Hull and Dominguez, 2006).…”
Section: Birdsmentioning
confidence: 98%
“…These males were then exposed in standardized test conditions to a sexually receptive female and their sexual behavior was recorded for 10 min. Their sexual behaviors were not obviously affected: the frequency of mount attempts and of cloacal contact movements were similar in control subjects and subjects with the occluded nares (Taziaux et al, 2008). Brains of experimental and control males were collected 90 min later and processed for imunohistochemical visualization of the Fos protein.…”
Section: Brain Activation By Social Semiosignalsmentioning
confidence: 95%
“…One study in Japanese quail ( Coturnix japonica ) indeed strongly suggests that olfactory inputs coming from the female modulate the metabolic activity of the medial preoptic nucleus (POM), a key brain region in the control of male sexual behavior (Taziaux et al, 2008). In this experiment, the nares of male quail were mechanically occluded (blocked with a layer of rapid- drying dental cement) and it was confirmed that they could no longer detect prominent olfactory stimuli such as the odor of acetic acid.…”
Section: Brain Activation By Social Semiosignalsmentioning
confidence: 99%
“…Therefore Japanese quails have been widely used for studies of different purposes [7][8][9] . Since Japanese quail is closely related to chickens, it is an ideal model organism as well [10,11] .…”
Section: Introductionmentioning
confidence: 99%